(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The levels of knowledge acquisition of students in the educational process can be classified as follows: • Entry level: students receive basic knowledge and basic concepts within the chosen field of knowledge. At this level, they will get acquainted with the basic theories and concepts associated with the field of Science and will have the initial skills to work in this field. • Intermediate level: at this stage, students continue to develop their knowledge and skills by delving deeper into the field of science. They deepen their knowledge, learn more complex and advanced theories and techniques, gain experience in independent work and research. • Higher level: at this stage, students become specialists in their subjects. They have deep knowledge, understanding and experience in their chosen field. At this level, students can actively participate in research, projects, and contribute to the academic community.